The Effect of Multiball Training and Hand Reaction Speed on the Accuracy of Forehand Drive Strokes in Table Tennis Games in West Sulawesi Polman Jaya Club Athletes - Nurnamira Nurnamira; Bambang Budi Raharjo; Andry Akhiruyanto (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
This study aims to analyze how the difference in the effect of constant pass multiball training and variable pass multiball training on the accuracy of forehand drive in table tennis games in West Sulawesi Polman Jaya club athletes, analyze how the difference in the effect of high hand reaction speed and low hand reaction speed on the accuracy of forehand drive in table tennis games in West Sulawesi Polman Jaya club athletes and analyze how is the interaction between the multiball training method and the speed of hand reaction to the accuracy of forehand drive strokes in table tennis games in athletes of the West Sulawesi Polman Jaya club. This type of research is an experiment with a 2 x 2 factorial design. The population of this study was 40 novice athletes from the active Polman Jaya club. The study sample was 28 athletes taken by purposive sampling technique. The data analysis technique used was a two-track Analysis of Variance (ANOVA) followed by the Tukey test with a significant level of α = 0.05. The results of the study are as follows. (1) There is a difference in the effect of constant pass multiball training method and variable pass multiball training method on the accuracy of forehand drive in table tennis games in novice athletes of Polman Jaya club, where the variable pass multiball training method is better than the constant pass multiball method, as evidenced by the value of p = 0.000 < 0.05. (2) There is a difference in the accuracy of forehand drive strokes in table tennis games in athletes who have high and low hand reaction speeds in beginner athletes of Polman Jaya club, where athletes who have high hand reaction speeds are better than athletes who have low hand reaction speeds, as evidenced by p = 0.000 < 0.05 values.